Effectiveness of Yoga-Based Cardiac Rehabilitation for Patients Undergoing Elective CABG Surgery: A Systematic Review - Veneranda Venny Grishela; Togu Deny Boy (Cerdika: Jurnal Ilmiah Indonesia, 2026)
CABG remains the standard revascularization procedure for advanced coronary artery disease; however, many patients continue to experience impaired functional capacity and reduced quality of life despite conventional rehabilitation. Yoga-based cardiac rehabilitation has emerged as a complementary intervention that may enhance postoperative recovery through integrated physical, respiratory, and mindfulness practices. This systematic review aimed to evaluate the effectiveness and safety of yoga-based cardiac rehabilitation in adults undergoing elective CABG surgery, focusing on cardiac function, functional capacity, autonomic regulation, cardiometabolic outcomes, quality of life, and long-term cardiovascular prognosis. A systematic review was conducted following the PRISMA 2020 guidelines. Literature searches were performed in PubMed, ScienceDirect, and the Cochrane Library to identify studies evaluating yoga-based rehabilitation in adults undergoing elective CABG surgery. Eligible studies were selected based on predefined PICOS criteria. Data regarding study characteristics, intervention protocols, and clinical outcomes were extracted and synthesized narratively. Seven studies met the eligibility criteria. The evidence indicated that yoga-based cardiac rehabilitation was associated with improvements in quality of life, functional capacity, autonomic regulation, psychological well-being, left ventricular ejection fraction, lipid profiles, glycemic control, inflammatory markers, and cortisol levels. Yoga Nidra demonstrated enhanced parasympathetic activity, while long-term follow-up suggested reduced all-cause mortality and a favorable trend toward fewer major adverse cardiovascular events. No serious adverse events were reported. Current evidence suggests that yoga-based cardiac rehabilitation is a safe and promising adjunct to conventional postoperative rehabilitation following elective CABG surgery, with potential benefits for physical, psychological, autonomic, and cardiometabolic outcomes. However, larger multicenter randomized controlled trials with standardized intervention protocols are required to strengthen the evidence base.